Phytochemical Analysis and Biological Activity of Euphorbia Hirta and Phyllanthus Watsonii - Daud, Mohd Nazrul Hisham (2006)
Preliminery screening for anti-inflammatory activity using 5-lipoxygenase assay has been carried out on 31 species of plant. From the results obtained, Euphorbia hirta and Phyllanthus watsonii two species of the Euphorbiaceae family showed high inhibition against enzyme 5-lipoxygenase. Based on this results, the phytochemical studies on both plants were carried out. Separation, isolation and purification of compounds from both species were done using solvent-solvent partitioning and chromatography techniques such as normal phase, gel filtration on sephadex LH-20 and reverse phase column chromatography. Two flavonoid O-gylcosides known as quercetin 3-O-rhamnoside [34] and myricetin 3-O-rhamnoside [35] were isolated from the ethyl acetate fraction of Euphorbia hirta. The compounds 26-nor-D:A-friedoolean-14-en-3β-ol [30] and glochidonol [36] have been isolated from Phyllanthus watsonii. All the compounds were tested for their inhibitory effect against 5-lipoxygenase enzyme and antioxidants activity using the ferric thiocyanate (FTC), thiobarbituric acid (TBA), free radical scavenging activity (DPPH) methods. Although the methanolic crude extracts of both plants showed potent inhibition of more than 65% on the 5-lipoxygenase assay, all the compounds isolated showed inhibition below this value. Quercetin 3-O-rhamnoside and myricetin 3-O-rhamnoside gave 19.0% and 16.0% inhibition against 5-lipoxygenase at the test concentration of 2.5mM. The compounds 26-nor-D:A-friedoolean-14-en-3β-ol [30] and glochidonol [36] showed 17.2% and 17.1% inhibition at the test concentrations of 0.24 and 0.22mM, respectively. Meanwhile, quercetin 3-O-rhamnoside [34] and glochidonol [36] showed strong antioxidant activity, giving 97.7% and 95.5% inhibition in the ferric thiocyanate (FTC) method. In the thiobarbituric acid (TBA) experiment both compounds also showed strong antioxidant activity, giving 92.8% and 92.5% inhibition. Finally the DPPH free radical scavenging activity experiment, quercetin 3-O-rhamnoside [34] gave 85.8 % inhibition at the test concentration of 100μM. The IC50 was calculated to 23.40μM.